Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1152/physiolgenomics.00014.2013
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine kinase and mtDNA depletion in human cardiomyopathy: epigenetic and translational evidence for energy starvation

Abstract: Koczor CA, Torres RA, Fields EJ, Boyd A, He S, Patel N, Lee EK, Samarel AM, Lewis W. Thymidine kinase and mtDNA depletion in human cardiomyopathy: epigenetic and translational evidence for energy starvation. Physiol Genomics 45: 590 -596, 2013. First published May 21, 2013 doi:10.1152/physiolgenomics.00014.2013.-This study addresses how depletion of human cardiac left ventricle (LV) mitochondrial DNA (mtDNA) and epigenetic nuclear DNA methylation promote cardiac dysfunction in human dilated cardiomyopathy (DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Some genetic models implicate higher PKC␣ activity in hypertrophic CM, while others suggest it plays no role (2,3,13). Our data support a decreased expression of PKC␣ in AZT-induced CM, though as we have seen in our previous studies, there may be additional regulation of protein activity posttranscriptionally (19).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Some genetic models implicate higher PKC␣ activity in hypertrophic CM, while others suggest it plays no role (2,3,13). Our data support a decreased expression of PKC␣ in AZT-induced CM, though as we have seen in our previous studies, there may be additional regulation of protein activity posttranscriptionally (19).…”
Section: Discussionsupporting
confidence: 84%
“…Our own studies and those of others have implicated changes in DNA methylation in the etiology of heart failure (17,19,(31)(32)(33). Because mitochondrial dysfunction has been observed in human congestive heart failure, a mechanism similar to the one observed here for altering DNA methylation may play a key role in human disease.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These validated targets are most likely involved in modifying DCM rather than independently causing disease. Furthermore, other authors found differentially methylated gene promoters and a depletion of mitochondrial DNA that resulted in a thymidine kinase deficiency in DCM hearts [61,62]. Indeed, investigating epigenetic mechanisms represents an attractive approach for finding novel mechanisms of disease.…”
Section: Molecular Basis Of Dilated Cardiomyopathy: Past and New Actorsmentioning
confidence: 99%